Chloride Ion Battery Review: Theoretical Calculations, State of the Art, Safety, Toxicity, and an Outlook towards Future Developments. Issue 21 (24th May 2017) - Gschwind, Fabienne; Euchner, Holger; Rodriguez‐Garcia, Gonzalo
Abstract : Batteries in which chloride ions act as shuttles have only been under investigation for a few years, but already several publications have dealt with this topic. In this review, we extensively report for the first time the state of the art, as well as research on chloride ion batteries and chloride conduction. In addition, we present a theoretical screening along with calculations of the capacities and volumetric and gravimetric densities, as well as an analysis of safety and toxicity. At the end, possible future approaches are evaluated. Abstract : This review is the first review about chloride ion batteries, in which the chloride ion (Cl – ) acts as shuttle. We present the state of the art, theoretical screening with calculations of the capacities and volumetric and gravimetric densities, and an analysis of safety and toxicity along with comparisons with other cell chemistries.